Analisis hambatan pada penyelesaian soal perkalian dan pembagian bilangan cacah di kelas II sekolah dasar - Hanandita, Tiara; Karlimah; Apriani, Ika Fitri (COLLASE (Creative of Learning Students Elementary Education), 2025)
This research aims to analyze students when solving multiplication and division of whole number problems. The subjects in the research focused on 24 class II students at SDN 3 Sukarindik, Kec. Bungursari, Tasikmalaya City. The data comes from students' answers after working on 5 essay questions on multiplication and division of whole numbers at easy, medium and difficult levels. The results of the research revealed the learning obstacles experienced in solving questions. It can be detailed as follows: (1) obstacles in understanding the concept of multiplication, (2) obstacles in understanding the concept of multiplication in story problems, (3) obstacles in understanding the concept of division, (4) obstacles in understanding the concept of division in story problems. This is shown by data from students who still have difficulty answering questions on multiplication and division of whole numbers, which reaches a percentage of 66.6%. The method used is a qualitative descriptive method and data collection techniques through interviews and test questions.